Paediatric ocular trauma in Kuching, Sarawak, Malaysia - Tan , A.K; P.S, Mallika; Asok, T.; S, Mohamad Aziz; G, Intan (Academy of Family Physicians of Malaysia, 2011)
Tan AK, PS Mallika, T Asokumaran, S Mohamad Aziz, G Intan